This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
To note the first observation use the Sophie-Germain identity to factor n 4 + 4 = n 4 + 4 ( 1 4 ) as ( n 2 + 2 + 2 n ) ( n 2 + 2 − 2 n ) to get the general term as ( n 2 + 2 + 2 n ) ( n 2 + 2 − 2 n ) n and then use partial fractions.
I prepared the same partial fraction...but how did the minus change to plus
Log in to reply
The expression on the final line takes the first terms for the cases n = 1 and n = 2 , since these are the only terms left after the sum is telescoped. I've re-formatted this line to better reflect this observation.
Exactly same way.
A typo first line first term. Denominator 4th power of n.
n 4 + 4 n = 4 1 ( n 2 − 2 n + 2 1 − n 2 + 2 n + 2 1 ) B y p a r t i a l f r a c t i o n s . ∴ 4 ∗ n 4 + 4 n = 1 ∑ ∞ n 2 − 2 n + 2 1 − 1 ∑ ∞ n 2 + 2 n + 2 1 = 1 ∑ 2 n 2 − 2 n + 2 1 + 3 ∑ ∞ n 2 − 2 n + 2 1 − 1 ∑ ∞ n 2 + 2 n + 2 1 = 1 + 2 1 + 1 ∑ ∞ n 2 + 2 n + 2 1 − 1 ∑ ∞ n 2 + 2 n + 2 1 = 2 3 . ∴ 1 ∑ ∞ n 4 + 4 n = 8 3 .
Upon solving the last step shows that substituting n with [n+2] we get the second term... So cancellation of terms begins every two times
Problem Loading...
Note Loading...
Set Loading...
Note first that
n 4 + 4 n = 4 1 ( n 2 − 2 n + 2 1 − n 2 + 2 n + 2 1 ) =
4 1 ( ( n − 1 ) 2 + 1 1 − ( n + 1 ) 2 + 1 1 ) .
When this is summed over the positive integers, we end up with a telescoping sum, with terms canceling pairwise and leaving us with only the first "parts" of the first two terms, i.e., we end up with
4 1 ( ( 1 − 1 ) 2 + 1 1 ) + 4 1 ( ( 2 − 1 ) 2 + 1 1 ) = 4 1 + 8 1 = 8 3 = 0 . 3 7 5 .